Bioethics and Culture: Understanding the Contemporary Crisis in Bioethics - SOLOMON, David (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. 生命倫理學與文化的關係是晚近生命倫理學討論的熱點話題。圍繞着布什生命倫理委員會 (President’s Council on Bioethics or Bush Bioethics Council) 的種種風波和爭議，使生命倫理學中的文化權威問題尤為突顯。本文將審查布什生命倫理委員會的性質，並從新的視角解釋為什麼圍繞該委員會的爭論會陷入如此激烈、不可調和的分裂中。我的新解釋是這些分裂與其說是生命倫理學政治化的結果，毋寧說是文化深層分歧在生命倫理學和道德哲學領域中的表達。 Much attention has been paid to the relation of bioethics and culture in recent years among those who primarily work in bioethics and also among those whose primary concerns are with matters of culture.1 Why? There are a number of reasons for this widespread interest, and in what follows I hope to explore the variety of these reasons and to suggest some ways of assessing the present state of this discussion. Among the conclusions of my discussion will be that the interplay between purely philosophical considerations bearing on contemporary discussions in bioethics and more general cultural considerations has been of the first importance in shaping recent developments in the emerging academic discipline of bioethics. One cannot ignore developments in academic moral philosophy if one hopes to understand why relations between bioethics and culture have been at the center of so many recent discussions. Also, I will suggest (but hardly establish) that the current unrest in bioethics centered on matters of its relation to culture grows ultimately out of deep cultural divisions and will not be easily resolved by mere adjustments in the methodology of bioethics or by “repackaging” bioethics. My strategy in this paper will be first to distinguish two quite difference sets of issues in the broad area of bioethics and culture and then discuss in some detail the second of these sets of issues. After exploring the second set of issues in a preliminary way I will relate them to some recent episodes in bioethics, in particular the vicious disagreements and lack of civility involved in the reaction of some establishment bioethicists to the deliberations of the Bush Bioethics Council.2 The depth of the disagreement and rancor in this case has led some to speak of a crisis in the field and of a need for some new methodological orientation for bioethics. Turning to a discussion of some general features of the history of bioethics since its creation half a century ago, I will suggest that these recent disturbances are rooted in features of bioethics present from its beginning. There has never been, as some suppose, a golden age when agreement was easy and mainstream bioethicists spoke with a single voice that commanded universal—or even near universal—assent. I will finally turn very briefly at the end of the paper to two important recent developments in the effort to reorient bioethics--the movement on the part of a number of establishment bioethicists to develop what they call Progressive Bioethics 3 and the sociologist John Evans’s recent proposal to draw on sociological insights to address the crisis in bioethics. I will argue that neither of these reforming proposals is adequate to resolve the difficulties in bioethics that elicited them. DOWNLOAD HISTORY | This article has been downloaded 78 times in Digital Commons before migrating into this platform.